2005
DOI: 10.1038/sj.ejcn.1602254
|View full text |Cite
|
Sign up to set email alerts
|

[6S]5-methyltetrahydrofolate or folic acid supplementation and absorption and initial elimination of folate in young and middle-aged adults

Abstract: Objectives: To assess the effects of supplementation with the diastereoisomer of 5-methyltetrahydrofolate ([6S]5-methylTHF), as an alternative supplement for folic acid, on folate absorption and elimination, in two age groups. Design: A randomized, double-blind intervention study. Subjects: A total of 12 young (o30 y) and 12 middle-aged (Z50 y) healthy volunteers were recruited. Methods: Volunteers were randomized to receive daily supplementation with 400 mg folic acid or equimolar amounts of [6S]5-methylTHF d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…One possible mechanism for the observed decline in plasma concentrations of unmetabolized folic acid is upregulation of folic acid metabolism [9, 50]. Kamen and colleagues found that, as compared to human liver cells in situ , the expression and activity of DHFR was 100- to 200-times higher in human cell lines in vitro and fresh rat liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism for the observed decline in plasma concentrations of unmetabolized folic acid is upregulation of folic acid metabolism [9, 50]. Kamen and colleagues found that, as compared to human liver cells in situ , the expression and activity of DHFR was 100- to 200-times higher in human cell lines in vitro and fresh rat liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this general acceptance, recent reports have questioned the validity of PteGlu as reference in AUC protocols Melse-Boonstra et al, 2004;Wright et al, 2005) since a substantial portion of the plasma response after consumption of 13 C 5 -PteGlu or 13 C 5 -5-formyltetrahydrofolate does not originate from the test dose, and secondly since plasma response kinetics among PteGlu and natural folates largely differ (Wright et al, 2003(Wright et al, , 2005. Alternatively, we considered [6S]-5-CH 3 H 4 PteGlu since its appearance in circulation is unlikely to depend on interconversion reactions (de Meer et al, 2005). It should be noted that using 'unlabeled' [6S]-5-CH 3 H 4 PteGlu did not allow a distinction between the response originating from the dose and the endogenous response caused by displacement of folate from body pools (Wright et al, 2003) and that interpretation of the current results is hence somewhat challenging.…”
Section: Serum Folate Response To Treatmentsmentioning
confidence: 99%
“…A total of 23 studies out of the original 5226 articles identified fit the full inclusion criteria and were appraised in this review. All studies provided quantitative data with 4 trials [19][20][21][22] using animal models and 19 studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] conducting human trials.…”
Section: Resultsmentioning
confidence: 99%